Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.48550/arxiv.1503.07921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking the News: First Impressions Matter on Online News

Abstract: A growing number of people are changing the way they consume news, replacing the traditional physical newspapers and magazines by their virtual online versions or/and weblogs. The interactivity and immediacy present in online news are changing the way news are being produced and exposed by media corporations. News websites have to create effective strategies to catch people's attention and attract their clicks. In this paper we investigate possible strategies used by online news corporations in the design of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…In essence, news behavior on this subreddit resembles news popularity in general. This work also shows that users tend to the change the news titles to be more positive and more analytical despite news being more negative overall [13]. When users change the titles of a news article, the article tends to become more popular.…”
Section: Related Workmentioning
confidence: 63%
“…In essence, news behavior on this subreddit resembles news popularity in general. This work also shows that users tend to the change the news titles to be more positive and more analytical despite news being more negative overall [13]. When users change the titles of a news article, the article tends to become more popular.…”
Section: Related Workmentioning
confidence: 63%
“…One recent study demonstrated that headline negativity and overall sentiment is important in news popularity. (Reis et al 2015). The authors extract sentiment features from the headlines of four major news sources and use the bit.ly API to infer popularity.…”
Section: Related Work News Popularitymentioning
confidence: 99%
“…SentiStrength is a machine learning based method that provides the polarity of sentiment, with -5 being very negative and +5 being very positive (Thelwall et al 2010). In previous work, it has been shown to work well with news data (Reis et al 2015). Vader-Sentiment is a lexicon and rule-based sentiment tool that is built for sentiment expressed on social media (Hutto and Gilbert 2014).…”
Section: Featuresmentioning
confidence: 99%
“…Psychologists have known that early impressions matter and that early biases affect users in what they learn in further impressions of the artifact (Digirolamo and Hintzman 1997) . Based on analysis of about 70,000 headlines, Reis et al confirmed that the sentiment of the headline could have a serious impact on how popular the story might become and the kind of discourse it encourages (Rieis et al 2015). These projects have reiterated how headlines can serve as influential shortcuts for readers that can subsequently guide their interpretation of the news (Tannenbaum 1953).…”
Section: Significance Of News Headlinesmentioning
confidence: 99%
“…To answer these questions, we focused on news headlines from Google's SERP data (see Figure 1). The headline of a news story is known to influence users' interpretation of the story's content (Tannenbaum 1953) and impact its popularity (Rieis et al 2015). We collected headlines using election-related search keywords as seen on Google's search engine across 20 locations spread throughout the US.…”
mentioning
confidence: 99%